BRIDGING INTENTIONS AND ACTIONS: THE ROLE OF BRAND IMAGE AND LOYALTY IN BRANDED AYURVEDIC SKINCARE PRODUCTS - Mayekar, Jayesh B.; Pednekar, Achut P. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Ayurvedic products deeply rooted in the ancient health system of ayurveda, emphasize achieving harmony between the body, mind, and spirit. With over 5,000 years of history, ayurveda offers a personalized approach to wellness, focusing on an individual’s unique constitution, or Prakriti, based on the balance of three doshas: Vata, Pitta, and Kapha. In today’s competitive landscape, branding is vital for Ayurvedic products, helping to build trust and mitigate consumer anxiety when preferred brands are unavailable. This study explores consumer behaviour towards branded ayurvedic skincare products using the Theory of Planned Behaviour framework. It examines how key TPB variables ATT, SN and PBC influence Purchase Intention, which acts as a bridge between these variables and Consumer Behaviour. Additionally, the study investigates the moderating effects of Brand Image and Brand Loyalty on the relationship between PI and CB. Data were gathered from 400 respondents and analyzed using Structural Equation Modelling in AMOS 24. The results indicate that ATT significantly impacts PI, while SN and PBC do not show a direct influence. However, PI strongly mediates the connection between TPB variables and CB. Whereas, BI and BL play significant moderating roles in strengthening the impact of PI on CB